Inclusion is a challenge in the processes of educational practices - Matos, Lucinea de Jesus; Brito, Luan de Jesus Matos de (Brazilian Journal of Science, 2022)
Inclusion translates into the school's ability to respond effectively to the learning gap between students. It demands that the school becomes a space for exchanges in which it favors the act of teaching and learning among all, creating conditions for everyone to participate in the process of building knowledge regardless of their particular characteristics. Inclusion also requires changes in school management, making it more democratic and participatory, understanding the school space as a true field of pedagogical and social actions, in which people dream together and share common projects. It is characterized by its collaborative character, developing values ​​and organizing the school space so that everyone can interact in it without inconvenience and embarrassment. The school that includes values ​​the social role of the student, as it rests on the principle of contribution. Teachers who face the challenge of inclusion realize that this process changes school life and the relationship with other members of their school, even modifying their training and personal and professional attitudes. The implementation of inclusive education implies recognizing students' differences and understanding that learning is built in cooperation.